Correlates of Gambling Behaviour Among Adolescents: The Role of Psychological Factors, School Behaviours, and Normative Perceptions - Mariaelisa Renna; Emina Mehanović; Giulia Giraudi; Alberto Sciutto; Erica Viola; Marco Martorana; Serena Vadrucci; Maria Ginechesi; Claudia Vullo; Adalgisa Ceccano; Chiara Andrà; Pietro Casella; et al. (Behavioral Sciences)
Background: Gambling risk behaviour is an emerging problem among adolescents. This study investigated the role of psychological factors, school behaviours, and normative perceptions as correlates of gambling among 12–14-year-old students in Italy. Methods: The study included 1822 students from 29 secondary schools in two Italian Regions (Piedmont and Lazio) who participated in the baseline survey of the experimental controlled trial “GAPUnplugged”. Results: The prevalence of gambling in the last 30 days was 36.4%. The mean age was 13.1 years. Multilevel mixed-effect regression models identified high positive attitudes, high performance beliefs, low risk perceptions toward gambling, friends’ gambling, friends’ approval of gambling, and gambling with friends as independent correlates of adolescent gambling behaviour. Conclusions: It appears essential to design and implement preventive strategies addressing these factors among early adolescents in order to reduce gambling behaviours and their consequences in later ages.